2007
DOI: 10.1007/s11252-007-0020-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of land use and land cover patterns on thermal conditions using landscape metrics in city of Indianapolis, United States

Abstract: Direct applications of remote sensing thermal infrared (TIR) data in landscape ecological research are rare due to limitations in the sensors, calibration, and difficulty in interpretation. Currently there is a general lack of methodology for examining the relationship between land surface temperatures (LST) derived from TIR data and landscape patterns extracted from optical sensors. A separation of landscapes into values directly related to their scale and signature is a key step. In this study, a Landsat ETM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(91 citation statements)
references
References 45 publications
3
86
1
1
Order By: Relevance
“…For this purpose, a large body of research (Chen et al, 2014;Connors et al, 2013;Li et al, 2011;Weng et al, 2007;Zhou et al, 2011) has focused on the relationship between surface UHIs and landscape patterns using landscape indices based on the concept of landscape ecology; that is, the theory that landscape patterns strongly affect and are affected by ecological processes (Turner, 1989). Composition and configuration, as two aspects of landscape patterns, were both tested (Chen et al, 2014;Connors et al, 2013;Zhou et al, 2011), with the conclusion that composition is more effective than configuration in influencing LSTs or surface urban heat islands (SUHIs) (Chen et al, 2014;Li et al, 2012;Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, a large body of research (Chen et al, 2014;Connors et al, 2013;Li et al, 2011;Weng et al, 2007;Zhou et al, 2011) has focused on the relationship between surface UHIs and landscape patterns using landscape indices based on the concept of landscape ecology; that is, the theory that landscape patterns strongly affect and are affected by ecological processes (Turner, 1989). Composition and configuration, as two aspects of landscape patterns, were both tested (Chen et al, 2014;Connors et al, 2013;Zhou et al, 2011), with the conclusion that composition is more effective than configuration in influencing LSTs or surface urban heat islands (SUHIs) (Chen et al, 2014;Li et al, 2012;Zhou et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The software FRAGSTATS developed by McGarigal et al (2012) has became widely used for calculating landscape metrics in many fields, ranging from evaluating land use/cover changes to analyze the effects of landscape pattern on different kinds of ecosystem services (Uuemaa et al, 2013). However, the number of landscape metrics used in previous studies has ranged from 2 to more than 10 (Cao et al, 2010;Connors et al, 2013;Li et al, 2012Li et al, , 2013Sun et al, 2012;Weng et al, 2007). Frequently used metrics have included: percentage of landscape (PLAND), mean patch size (MPS), perimeter-area fractal dimension (PAFRAC), aggregation index (AI), cohesion index (COHESION), contagion index (CONTAG), and Shannon's diversity index (SHDI).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike in Freetown, the growth of Bo town has led to a reduction in the area of the densely vegetated LULC category between 1985 and 2015. As observed in Bo town, in most studies, the proportion of total area occupied by dense vegetation decreases with continuous urban expansion [26,27,53,54]. Kamusoko et al [54] observed that the expansion of built-up areas in Harare Zimbabwe pushed most dense vegetation locations outwards to the peripheries of the city.…”
Section: Discussionmentioning
confidence: 88%
“…The steps as summarised by Weng et al [26] and described in detail by Weng et al [44] are followed to retrieve the land surface temperature from Landsat's thermal infrared data. The procedure involved (i) conversion of digital numbers (DN) to spectral radiance; (ii) computation of satellite brightness temperature from spectral radiance; and (iii) retrieval of land surface temperature from brightness temperature (emissivity correction).…”
Section: Lst Retrieval From Thermal Infrared Datamentioning
confidence: 99%